Pertumbuhan Ekonomi Regional : Studi Kasus Analisis Konvergensi Antar Propinsi di Indonesia - Jamzani Sodik (Economic Journal of Emerging Markets, 2006)
This paper examines the determinants of regional economic growth in Indonesia, and test for convergence PDRB per capita 26 province the period 1993 to 2003, using GLS method (General Least Square) for process polling data. Factor that affect the regional economic growth are initial level of PDRB riil per capita(X1), health(X2), education(X3), density(X3), and economic indicator: foreign direct investments (X4), rate openness economic province (X5), and inflation rate (X6).The results found regional economic growth for periods 1993-2003 are influenced by density(X3), rate openness economic province (X5), and inflation rate (X6). However health(X2), and  education(X3) not affect to regional economic growth.We find also evidence of absolute convergence and conditional convergence, however sigma ( ) convergence fluktuatif  for periods 1993-2003.Keywords : regional economic growth, convergence, and panel data